Shine : the visual economy of light in African diasporic aesthetic practice - Thompson, Krista A., 1972- (Duke University Press, 2015)
In Jamaican dancehalls competition for the video camera's light is stiff, so much so that dancers sometimes bleach their skin to enhance their visibility. In the Bahamas, tuxedoed students roll into prom in tricked-out sedans, staging grand red-carpet entrances that are designed to ensure they are seen being photographed. Throughout the United States and Jamaica friends pose in front of hand-painted backgrounds of Tupac, flashy cars, or brand-name products popularized in hip-hop culture in countless makeshift roadside photography studios. And visual artists such as Kehinde Wiley remix the.